ANALYSIS OF THE ROLE OF REGIONAL GOVERNMENT IN THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) DURING THE COVID-19 PANDEMIC FOR THE ECONOMY IN KENDARI - sasmita nabila syahrir; Yuyun Anggraini; Nekstriani; Mardiana; Surianto Ilham (Jurnal Akuntansi dan Keuangan, 2024)
At the end of 2020, when the Covid-19 pandemic first entered Indonesia, in Kendari City in particular, Micro, Small and Medium Enterprises (MSMEs) actually increased, this is proven by data on the development of MSMEs in Kendari City which was released by the City Department of Trade and Cooperatives Kendari 2023. Where in 2019 there were 14,757 MSMEs and in 2020 there were 34,247 MSMEs. In accordance with Law of the Republic of Indonesia Number 20 of 2008 concerning MSMEs, the Regional Government cannot be separated from efforts to develop and foster MSMEs. This research analyzes the government's role in developing Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic in Kendari City. This research use desciptive qualitative approach. Research object at the Cooperative and SME Trade Service in Kendari City. This research focuses on the role of local government in the development of Micro, Small and Medium Enterprises (MSMEs) located in Kendari City (Southeast Sulawesi). The results of this research are the role of the Cooperative Trade Service (Disperdagkop) and UKM as the Kendari City Regional Government in developing MSMEs by carrying out various programs, namely in the form of Micro Business Productive Assistance (BPUM), Special Allocation Fund Assistance (DAK), Provincial Stimulus Fund Assistance and Development Based on the research that has been carried out, the Regional Government has carried out its role well, so that it can advance the economy in Kendari City. This can be seen from the increase in the number of MSMEs from year to year during the Covid-19 pandemic . Keywords: Role of Regional Government, Covid-19 Pandemic, MSME Development, Economy.